Influenza Virus Infection Induces ZBP1 Expression and Necroptosis in Mouse Lungs - Wang, Yun; Hao, Qin; Florence, Jon M.; Jung, Bock-Gie; Kurdowska, Anna K.; Samten, Buka; Idell, Steven; Tang, Hua (Frontiers in Cellular and Infection Microbiology, 2019)
Programmed cell death and especially necroptosis, a programmed and regulated form of necrosis, have been recently implicated in the progression and outcomes of influenza in mouse models. Moreover, Z-DNA/RNA binding protein 1 (ZBP1) has been identified as a key signaling molecule for necroptosis induced by influenza A virus (IAV). Direct evidence of IAV-induced necroptosis has not been shown in infected lungs in vivo. It is also unclear as to what cell types undergo necroptosis during pulmonary IAV infection and whether ZBP1 expression can be regulated by inflammatory mediators. In this study, we found that IAV infection induced ZBP1 expression in mouse lungs. We identified that mediators implicated in the pathogenesis of IAV infection including interferons (IFNs), TNFa, and agonists for Toll-like receptors 3 and 4 were potent inducers of ZBP1 expression in primary murine alveolar epithelial cells, bone marrow derived macrophages and dendritic cells. We further found that IAV infection induced a strong necroptosis through phosphorylation of the necroptosis effector mixed lineage kinase domain-like protein in infiltrating immune cells and alveolar epithelial cells by day 7 post-infection. Lastly, we found different cell type-specific responses to IAV-induced cell death upon inhibition of caspases and/or necroptosis pathways. Our findings provide direct evidence that IAV infection induces necroptosis in mouse lungs, which may involve local induction of ZBP1 and different programmed cell death signaling mechanisms in alveolar epithelial and infiltrating inflammatory cells in the lungs.